Pelaksanaan Pengawasan oleh Direktorat Jendral Bea Cukai Terhadap Larangan Thrifting Pakaian Bekas Impor - Wulandari, Anugrah Kurnia; Harun, Harun; Susila, Jaka (Universitas Batanghari Jambi, 2024)
The purpose of this research report is to understand the procedures for implementing controls on the ban on thrifting of imported used clothing and to identify the factors that regulate the control of export and import activities by customs and tax authorities and hinder these bodies. The method used in this research is a qualitative method with a normative-empirical approach and the materials used include primary, secondary and tertiary data collection techniques, therefore based on observation, literature and documentation. The results of the investigation show: 1) the emergence of a period of supervision of correspondence with identification (scanning dogs or drug detectors), then inspections were carried out by all relevant agencies, maritime and maritime authorities, in the cases specified in Order Number PER -17/BC/2020 concerning procedures how to control the Director of Taxes and Customs. 2) Placement of customs and tax officers in the free zone (KB) hall through a computerized storage system and CCTV monitoring system, so that the company has a computerized inventory information system that cannot be differentiated from the existence of various types of warehouses. favorable and unfavorable factors.